Monitoring of the functional properties and unfolding change of Ovalbumin after DHPM treatment by HDX and FTICR MS: Functionality and unfolding of Oval after DHPM by HDX and FTICR MS. (15th July 2017) - Liu, Guang-xian; Tu, Zong-cai; Wang, Hui; Zhang, Lu; Huang, Tao; Ma, Da
Highlights: Surface activity promotion was observed after 120 MPa DHPM treatment. More flexible conformation was induced by DHPM. The big β-sheet including six strands is unaffected by DHPM. We hypothesized that "partial unfolding" could be caused by DHPM treatment. Abstract: Dynamic high-pressure microfluidizaiton (DHPM) induced unfolding of proteins and enzymes could enhance the functional properties and hydrolytic ability of the molecules. In this study, the effect of DHPM on the surface activities of Ovalbumin (Oval), namely foaming and emulsifying properties, was investigated at 0, 40, 80, 120 and 160 MPa. Improvement in the foaming and emulsifying properties was observed at 120 and 80 MPa, respectively. Hydrogen/deuterium exchange (HDX) coupled with Fourier transform infrared spectroscopy–mass spectrometry (FTICR MS) was performed to investigate the exact unfolded region of Oval and analyze the mechanism promoting the foaming and emulsifying properties after 120 and 80 MPa, respectively, compared with those at 0 MPa. Prevalent unfolding of Oval after 80 and 120 MPa treatment was revealed by HDX-MS, indicating a more flexible conformation induced by DHPM. However, lower deuterium incorporation was observed for the large six-stranded β -sheet. Therefore, the combined forces could enhance the flexibility and surface activities of Oval, which increased its foaming and emulsifying properties.